A Hexagonal Planar Metal Complex. Issue 11 (24th January 2020) - Tauchert, Michael E.; Okuda, Jun
Abstract: A six‐coordinate [ML3 Z3 ]‐type transition‐metal complex with a hexagonal planar geometry has been isolated and characterized, extending the scope of six‐coordinate metal coordination compounds to those with a geometry beyond octahedral and trigonal prismatic. Abstract : Flattened : A six‐coordinate [ML3 Z3 ]‐type transition‐metal complex with a hexagonal planar geometry has been isolated and characterized, extending the scope of six‐coordinate metal coordination compounds to those with a geometry beyond octahedral and trigonal prismatic.